No evidence for higher risk of cancer in patients with multiple sclerosis taking cladribine. Issue 6 (December 2015) - Pakpoor, Julia; Disanto, Giulio; Altmann, Daniel R.; Pavitt, Sue; Turner, Benjamin P.; Marta, Monica; Juliusson, Gunnar; Baker, David; Chataway, Jeremy; Schmierer, Klaus
Abstract : Objective: To compare the cancer risk of cladribine and other disease-modifying drugs (DMDs) in trials of people with relapsing multiple sclerosis (pwRMS). Methods: Meta-analysis of phase III trials of licensed DMDs for pwRMS and a phase III trial of cladribine (CLARITY). Cancer rates were compared using Fisher exact test. Results: Eleven trials were included. Investigated treatments included cladribine, dimethyl fumarate, fingolimod, teriflunomide, natalizumab, alemtuzumab, and glatiramer acetate. The cancer rate in the CLARITY treatment group (0.34%) was not increased compared to all other treatment groups, whether including placebo-controlled trials only (0.6%, p = 0.4631) or all trials, i.e., including those with an active comparator arm (0.67%, p = 0.3669). No cancer was reported in the CLARITY placebo group, whereas the combined cancer rate of all other placebo groups was 1.19% ( p = 0.0159). The cancer rate of zero in the CLARITY placebo group was also lower than that in the phase III trial of cladribine in people with clinically isolated syndrome (ORACLE MS, 2.91%, p = 0.0012). In fact, no difference was detected between cancer rates in the treatment groups of CLARITY (0.34%) and ORACLE MS (0.49%) ( p = 0.6546). Conclusions: Our study does not support an increased cancer risk from cladribine in the doses used in CLARITY and ORACLE MS, which previously contributed to refusal of market authorization of cladribine in Europe. Longer-term follow-up is required to assess the safety profile of cladribine, as well as currently licensed DMDs, to definitively assess cancer risk.